2018
DOI: 10.1002/ijfe.1608
|View full text |Cite
|
Sign up to set email alerts
|

Examining drivers of trading volume in European markets

Abstract: This study presents an in-depth exploration of market dynamics and analyses potential drivers of trading volume. The study considers established facts from the literature, such as calendar anomalies, the correlation between volume and price change, and this relation's asymmetry, while proposing a variety of time series models. The results identified some key volume predictors, such as the lagged time series volume data and historical price indicators (e.g. intraday range, intraday return, and overnight return)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
3
6
0
1
Order By: Relevance
“…It is hypothesized in the current study that investors will become more risk-averse and cut back on their stock market trading activity if the market has recently seen poor performance. This theory is in line with previous research on investors' reactions to market shifts (Batrinca, Hesse & Treleaven, 2018). This would mean that investors' decisions about whether or not to put money into the stock market would be driven by the ups and downs of the market index and the performance of individual stocks.…”
Section: Literature Reviewsupporting
confidence: 85%
See 1 more Smart Citation
“…It is hypothesized in the current study that investors will become more risk-averse and cut back on their stock market trading activity if the market has recently seen poor performance. This theory is in line with previous research on investors' reactions to market shifts (Batrinca, Hesse & Treleaven, 2018). This would mean that investors' decisions about whether or not to put money into the stock market would be driven by the ups and downs of the market index and the performance of individual stocks.…”
Section: Literature Reviewsupporting
confidence: 85%
“…This proved that investors' faith in the stock market was being impacted by the state of the economy. Because of the belief that a recession will lead to a drop in stock market performance, investor sentiment and behavior tend to adopt a more cautious tack during this time (Batrinca, Hesse & Treleaven, 2018). Due to the high level of uncertainty, which can result in a high level of exposure to potential loss, investors are typically advised to decrease their desire to invest in the stock market.…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong seasonal behaviour of the liquidity premium (Batrinca, Hesse, & Treleaven, 2018;Eleswarapu & Reinganum, 1993), we adapt the approach followed by Jagannathan and Wang (2007) and switch our final series to an annual basis.…”
Section: Resultsmentioning
confidence: 99%
“…Such research has proposed a day of the week effect (Monday effect), where market returns are poorer on Mondays (French, 1980). There is mixed evidence of a universal day of the week effect (Dicle & Levendis, 2014) but there is evidence that markets have less trading activity on Mondays compared to other days of the week (Batrinca et al, 2018;Foster & Viswanathan, 1993). Our findings show that individual investors follow a different trend; they are more likely to trade on a Monday and they are more likely to sell on a Monday than any other day of the week.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Batrinca, Hesse, and Treleaven (2018) conducted an analysis on pan-European stock markets which comprised of 7,197,065 daily observations for the period between 1 January 2000 and 10 May 2015. They found that the trading volume on Monday was less than other days of the week.…”
Section: Market Trading Activity Over Days Of the Weekmentioning
confidence: 99%